Radon concentration in air and external gamma dose rate: is there a correlation? - Yoshimura, Elisabeth (2015)
We checked the existence of correlations between experimentally determined radon concentration in indoor air and gamma dose rate, in different environments: residences, workplaces in subway stations and radiotherapies, and a gold mine. Except for the mine environment, where a linear correlation (r2 = 0.86) was obtained with statistical significance, we found no correlations between those quantities. Both radiation sources are originated from natural radionuclides, nonetheless the observation of correlations depends on various conditions, as we discuss here